MOMBESARA DISCOURSE IN WEDDING CEREMONIES OF TOLAKINESE SOCIETY - Disa Arliwan (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
The objectives of this study are: 1) To provide an overview of the meaning contained in the public discourse. 2) To provide an overview of the values ​​contained in the mombesara discourse as a medium of communication in the traditional ceremony of the Tolaki community. This research is a qualitative naturalistic study. This study focuses on the uns stilistic mombesara discourse. The way to choose the choice of vocabulary (lexicon), which is how the words are used in the public discourse. The results of this study indicate that language in the mombesara discourse as a medium of communication in Tolaki society is full of meaning. Language in mombesara discourse is full of blistering and symbolic language, which is not able to fulfill its meaning by most people. In many mombesara discourses discussed, diction and style of language used. In addition, the mombesara discourse also holds the cultural values ​​of the Tolaki community which are used as instructions and instructions in the practice of involvement in 1) Religious values, 2) Values ​​of courtesy, 3) Value of responsibility, and 4) Value of pride